Contextual Social Interaction and Persuasive Strategy: Vital Facets of Older Adults' Interpersonal Relationship in Institutional Residence - Endah Dwi Winarni (Asian Social Work Journal, 2018)
This study discusses the dynamic of older adults’ interpersonal relationship in institutional residence. Several similar studies tended to analyze benefits of interpersonal relationship for older adults in institutional residence, types of social interaction between older adults in institutional residence, and common conversations between older adults in institutional residence. Those studies did not explore the ways to stimulate associative social interaction of older adults in institutional residence. Whereas, those ways are meaningful due to both older adults’ body and mental functions have degenerated, so it makes them vulnerable to interact. Therefore, this study aims to fill that lack. This study argues the older adults’ interpersonal relationship in institutional residence should be elaborated by contextual social interaction and persuasive strategy complementarily. This study uses a qualitative approach and conducted a case study at Jiwa Baru social protection residence, Garut, Indonesia. The finding is showed there are three context that form social interaction of older adults in institutional residence, namely personal instruments, structure, and culture; then, by understanding the process of social interaction was formed, can be formulized persuasive strategy to stimulate associative social interaction of older adults in institutional residence, e.g, persuaded by a closest friend, provide both a suitable assistance and care, create an interactive culture, and build a sense of community.